ZADANIA MUNICIPIUM W ŚWIETLE LEX IRNITANA. PRZYCZYNEK DO STUDIÓW NAD PRAWEM MUNICYPALNYM W STAROŻYTNYM RZYMIE - Sitek, Bronisław (Zeszyty Prawnicze, 2017)
Tasks of municipium in lex Irnitana. Studies on Municipal Law in Ancient Rome Summary The paper presents the tasks of municipium set in lex Irnitana. Inparticular it touches upon the questions of munera publica and the tasks ofmunicipality, cura annonae, local security, duties connected with privatetransactions, legations, public cult, legislature and administration ofjustice. The analysis of lex Irnitana provides an insight into the ancient conceptof municipium, viz., structure of a local society. It shared some elementswith the republican system, however, with alterations implied by the newpolitical regime. Although the idea of legal personality was not known inRoman law, municipium functioned as if it was a legal entity: it had organsandduties. Further analysis of lex Irnitana shows that local authorities had, to some extent, a legislative power, which was exercised by decuriones andduoviri. Aediles were responsible for the security on roads, at bazaars andtheatres. It is characteristic for the antiquity that local authorities had somejudiciary power, and duovirs adjudicated in less significant cases. Othertypes of cases were adjudicated by the governor of a province. Munera publica, that is public duties, were performed by the magistrate, since in Rome the idea of tasks of municipality was not known. It is possible to ascertain that there is a significant similarity between the range of tasks of local societies, especially municipalities, in Rome and the duties set forth in contemporary self-government bills.